System and method for navigating search results - Blazejewski, Edward; Kuo, Chao-Hen; Kenney, Joseph; Angle, Thomas (2007)
A method for navigating search results includes identifying a first occurrence and a second occurrence of at least one search term in a document. The method also includes generating a web page comprising at least a portion of the document. The first occurrence appears as a hyperlink in the web page. The hyperlink is associated with a position of the second occurrence. The method further includes communicating the web page for display to a user.